Reskilling Tenaga Kerja: Strategi Kebijakan Menghadapi Pengangguran Akibat Revolusi Industri 4.0 - Dasmadi Dasmadi; Nico Djundharto Djajasinga; Yane Mayasari; Sri Suparni; Iman Ahmad Gymnastiar (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The development of the times and technology has led to an increase in efficiency in the world of work. But at the same time, the existence of this technology then slowly begins to replace some human jobs. Therefore, there is a need for reskilling in the workforce to reduce the number of unemployed caused by the industrial revolution 4.0. This research then aims to look at how policy strategies can be made to help implement workforce reskilling. This research will be carried out using a descriptive qualitative approach. This research method is a literature study using data from previous research which still has relevance to the contents of this research. The results of this study then found that through collaboration between the government and stakeholders, the government can anticipate changes in job trends and help develop new skills needed by the unemployed. By ensuring skills match job trends, individuals will be better prepared to deal with the changes that occur and increase their chances of finding jobs that match market needs. However, unfortunately the implementation of the reskilling policy still encounters several obstacles, such as a lack of resources and gaps in access owned by the community.